Gender Adjustment for Sustainable City (Case of 3G (Glintung Go Green) in Malang City) - Nuh, Muhammad; Cahyasari, Erlita; Lastiti Veri Anggaini, Niken; Winoto, Suhartono (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2018)
Gender issue always become an interesting topic to be researched, especially when the gender issue itself is related to sustainable city issue. Sustainability of a city cannot be separated from gender role and contribution. The existence of gender often becoming influential group in city living environment. In one part of Malang City, at Kelurahan Purwantoro, initiating a Water Saving Movement or Gerakan Menabung Air (Gemar) at Kampung 3G (Glintung Go Green). The purpose of this research is to provide the relationship representation between gender and sustainable city program, especially in succeeding the activity at Kampung 3G (Glintung Go Green). This research using descriptive quantitative method, with questionnaire as the data gathering method in knowing the gender role and perception. This research also using SPSS to analyze the data. The result shows that there is a significant relation between gender and Kampung 3G sustainable city program, however the successes and development of the program did not affecting gender perception. It also shows that the successes of sustainable city program is not in line with the development of gender perception.